Fungal footprints in oral cancer: unveiling the oral mycobiome - Monteiro, Jessica Sonal; Kaushik, Kriti; de Arruda, José Alcides Almeida; Georgakopoulou, Eleni; Vieira, Angelica Thomaz; Silva, Tarcilia A.; Devadiga, Darshana; Anyanechi, Charles E.; Shetty, Sameep (Frontiers in Oral Health, 2024)
Oral squamous cell carcinoma (OSCC) is the most common type of head and neck cancer, with a high mortality rate. There is growing evidence supporting a link between oral cancer and the microbiome. The microbiome can impact various aspects of cancer, such as pathogenesis, diagnosis, treatment, and prognosis. While there is existing information on bacteria and its connection to oral cancer, the fungi residing in the oral cavity represent a significant component of the microbiome that remains in its early stages of exploration and understanding. Fungi comprise a minuscule part of the human microbiome called the mycobiome. Mycobiome is ubiquitous in the human body but a weakened immune system offers a leeway space for fungi to showcase its virulence. The role of mycobiome as a colonizer, facilitator, or driver of carcinogenesis is still ambiguous. Reactivating the mycobiome that undergoes collateral damage associated with cancer treatment can be watershed event in cancer research. The coordinated, virulent, non-virulent behavior of the fungi once they reach a critical density must be hacked, considering its diagnostic, prognostic and therapeutic implications in cancer. This review highlights the diversity of the mycobiome and its potential role in oral cancer.